Black bear spatial responses to the Wallow Wildfire in Arizona. Issue 3 (19th January 2022) - Crabb, Michelle L.; Clement, Matthew J.; Jones, Andrew S.; Bristow, Kirby D.; Harding, Larisa E.
Abstract: The Wallow Fire, the largest wildfire in Arizona history, encompassed 2, 170 km 2 and provided a rare opportunity to examine habitat selection and home ranges of American black bears ( Ursus americanus ) before and after a wildfire. We had fitted global positioning system (GPS) collars on 47 bears from 2005 to April 2011, and 10 of these were still collared when the fire started in May 2011. We captured and collared an additional 7 black bears within the fire perimeter post‐fire (Jul–Sep 2011 and Jun 2012). To evaluate how black bears were affected by the fire, we fit a step selection function using a conditional mixed effects Poisson regression model to estimate the relative strength of black bear habitat selection in response to burn severity. Additionally, we estimated home range sizes using an autocorrelated kernel density estimator by means of a continuous‐time movement model. We then used a generalized linear model with a negative binomial error distribution and mixed effects to estimate the effect of the burn severity on black bear home range size, while controlling for sex and drought. In spring and summer in years prior to the fire, bears selected areas that later burned in the fire. After the fire, bears used all burn severities, but their selection for high‐severity burns decreased significantly in summer 2011 and fall 2012. Home range sizes were 3.06 times larger pre‐fire than post‐fire. Our study demonstrates that black bears continued to use all burn severities after a major wildfire, and that post‐fire conditions did not result in expanded black bear home ranges. Abstract : Following the largest wildfire in Arizona history, black bears selected unburned and lower severity burned areas, though season had a significant effect on selection of burn severity classes. Black bear home ranges were larger pre‐ than post‐fire.